2018
DOI: 10.3390/su10020550
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficiency of Limestone Powder in Concrete and the Effects on the Environment

Abstract: Abstract:The major environmental impact of concrete comes from the CO 2 emissions, produced during the cement manufacturing process. The main goal of this research project is to evaluate the efficiency of limestone powder as a partial cement replacement, in order to reduce energy consumption and CO 2 emissions. This study utilizes limestone powders, with different particle sizes, to replace a portion of Portland cement using various ratios. Due to the dilution effect when partially replacing cement, there is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…While it is possible to add more calcium carbonate according to the European Standard (EN 197-1:2011(EN 197-1: , 2011, 15% was used in this calculation as it provides near equivalent strength to that of the OPC considered in this study. Comparatively the associated emissions of ground limestone range from 24.5-90.7 kgCO 2 /kg of limestone, depending on grind quality (Kim et al, 2018). At 15% limestone substitution this would equate 0.77-0.78 kgCO 2 /kg of blended cement dependent on grind quality.…”
Section: Results and Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is possible to add more calcium carbonate according to the European Standard (EN 197-1:2011(EN 197-1: , 2011, 15% was used in this calculation as it provides near equivalent strength to that of the OPC considered in this study. Comparatively the associated emissions of ground limestone range from 24.5-90.7 kgCO 2 /kg of limestone, depending on grind quality (Kim et al, 2018). At 15% limestone substitution this would equate 0.77-0.78 kgCO 2 /kg of blended cement dependent on grind quality.…”
Section: Results and Interpretationmentioning
confidence: 99%
“…Portland cements blended with upto 35% limestone or SCMs have overtaken OPC in terms of market share (Schmidt et al, 2013). The grinding of limestone is the primary source of carbon emissions associated with its use: 24-90 kg CO 2 /tonne depending on final particle size (Kim et al, 2018) while the other miscellaneous processes are approximated to emit 2.76 kgCO 2 /tonne by Kittipongvises (2017) as well as lower emissions of other pollutants such as NOx and SOx as detailed in their compre-hensive analysis of limestone quarrying operations (Kittipongvises, 2017). By producing calcium carbonate directly from the Portland cement emissions it is believed that greater reductions of CO 2 emissions compared to limestone can be achieved.…”
Section: Graphical Abstractmentioning
confidence: 99%
“…Liquid phase (paste volume) has affected the slump flow diameter. It could be easily achieved (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) MPa compressive strength with cement replacement up to 15% by LSP.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, LSP has a positive effect on the compressive strength once the quantity of LSP increases [5], [9], [11], [16], [18], [20], [30], [37], [39], [40]. However, a reduction on compressive strength due to LSP has been noticed [19], [25], [34]- [36], [41], [42]. Mahmoud et al [43] stated that, 50-60 MPa compressive strength of SCC could be achieved using 450 Kg/m 3 powder content with 33% cement replacement by LSP.…”
Section: Introductionmentioning
confidence: 99%
“…However, during cement production, around 0.8 tons of carbon dioxide are released into the atmosphere per ton of cement. Furthermore, it is now reported that approximately 2-8% of global electricity consumption is attributed to the cement manufacturing process (Kim et al, 2018;N. Mohamad et al, 2021;Nilimaa, 2023;Yong et al, 2021).…”
Section: Introductionmentioning
confidence: 99%